Design of Balanced Scorecard as a School’s Performance Measurement - Lily Ambarwati Saksono; Denny Bernardus (Binus Business Review, 2023)
For schools as educational institutions, it is essential to identify their conditions and determine the right strategy for their sustainability. The research aimed to design the Balanced Scorecard (BSC) as a performance measurement tool at Sekolah XYZ. The research applied a qualitative method with Simple Research Design (SRD) as an analytical model. For data analysis, the research applied the stages of preparation in BSC. The primary data collection method was conducted through interviews with five key informants. The measurement indicators consisted of five indicators from a financial perspective (weight: 25%), three indicators from a customer perspective (weight: 25%), nine indicators from an internal business process perspective (weight: 30%), and five measurement indicators from the learning and growth perspective (weight: 20%). In addition, the BSC design was equipped with a validation system and an evaluation system to support the BSC implementation at Sekolah XYZ. The results show that based on the vision and mission of the organization, there are 12 objective strategies to be achieved, with 22 measurement indicators that are appropriately implemented at Sekolah XYZs. The BSC at Sekolah XYZ is necessary to be designed so its management can easily trace and find the causes of the school’s success or failure. The results of the BSC design at Sekolah XYZ can be used as recommendations for other schools that want to implement BSC, with adjustments according to the conditions of each school.